Polyvinyl chloride gel based electro-active switchable bio-inspired adhesive. (December 2022) - He, Qingsong; Pan, Hui; Zhao, Zefang; Zhang, Hao; Yin, Guoxiao; Wu, Yuwei; Cai, Lei; Yu, Min; Duan, Jinjun; Shen, Qi; Deng, Kai; Dai, Zhendong
Graphical abstract: Abstract: Controlled attachment and detachment mechanisms of geckos have been the focus of attention for decades. Although great progress has been made in the fabrication of biomimetic adhesive materials, dynamically switchable adhesion is still challenging. In this work, inspired by the active muscular locomotion of gecko toes, a novel switchable electro-active adhesive based on polyvinyl chloride (PVC) gel was successfully prepared, including PVC gel active backing layer and a passive PVC fibrillar adhesive layer. The performance of PVC gel actuator, adhesive, and electro-active adhesive are stable. Due to the active backing layer and adhesive layer are all made by PVC gel, the strong bonding between two layers was achieved. Compared with reported reversible adhesive, it exhibited greater adhesion force and response speed. Furthermore, a flexible gripper was made, and the grasping test was successfully carried out. This work provides a new technology for micro/nano manipulation, transfer printing, and climbing robot applications.